Single‐Cell Transcriptomic Analysis Demonstrates the Regulation of Peach Polysaccharides on Circadian Rhythm Disturbance. Issue 14 (31st May 2022) - Sun, Qiaoyu; Xu, Wenqing; Liu, Yanan; Zhan, Shengnan; Shao, Xingfeng; Wu, Zufang; Weng, Peifang; Cheng, Kejun; Zhang, Xin
Abstract : Scope: Plant polysaccharides are thought to have a prebiotic effect, promoting the growth of probiotics, which may regulate circadian rhythms. This study evaluates the regulation of peach polysaccharides (PPS) on circadian rhythm disturbance through intestinal microbiota by a mouse model. Methods and results: PPS is administered to mice with circadian rhythm disturbance for 4 weeks. The study finds that PPS ameliorated the structural disorder of intestinal microbiota induced by continuous darkness, decreasing the ratio of Firmicutes / Bacteroidetes (F/B), thereby regulating furfural degradation, penicillin and cephalosporin biosynthesis, and antibiotic biosynthesis. Single‐cell transcriptomics is used to determine the type of hypothalamus cells and the expression of clock genes in mice, showing that the number of astrocytes and oligoendrocytes cells in the hypothalamus of the transplanted mice is up‐regulated, and the expression of neuroprotective genes such as Sox9 and Mobp increased. In addition, clock genes such as Cry2 and Per3 show significant callback. Conclusion: This study shows that PPS can ameliorate the imbalance of intestinal microbiota and cell dysfunction caused by circadian rhythm disorder, suggesting that PPS is a feasible strategy for the prevention and treatment of circadian rhythm disorder and related cognitive impairment. Abstract : PPS has a positive effect on circadian rhythm disorder and its associated cognitive decline by regulating intestinal microbiota diversity and metabolites.